Molecular, immunological, and biological characterization of Tityus serrulatus venom hyaluronidase: new insights into its role in envenomation. - Carolina Campolina Rebello Horta; Bárbara de Freitas Magalhães; Bárbara Bruna Ribeiro Oliveira-Mendes; Anderson Oliveira do Carmo; Clara Guerra Duarte; Liza Figueiredo Felicori; Ricardo Andrez Machado-; Carlos Chávez-Olórtegui; Evanguedes Kalapothakis (Public Library of Science (PLoS), 2014)
BACKGROUND: Scorpionism is a public health problem in Brazil, and Tityus serrulatus (Ts) is primarily responsible for severe accidents. The main toxic components of Ts venom are low-molecular-weight neurotoxins; however, the venom also contains poorly characterized high-molecular-weight enzymes. Hyaluronidase is one such enzyme that has been poorly characterized. METHODS AND PRINCIPAL FINDINGS: We examined clones from a cDNA library of the Ts venom gland and described two novel isoforms of hyaluronidase, TsHyal-1 and TsHyal-2. The isoforms are 83% identical, and alignment of their predicted amino acid sequences with other hyaluronidases showed conserved residues between evolutionarily distant organisms. We performed gel filtration followed by reversed-phase chromatography to purify native hyaluronidase from Ts venom. Purified native Ts hyaluronidase was used to produce anti-hyaluronidase serum in rabbits. As little as 0.94 µl of anti-hyaluronidase serum neutralized 1 LD50 (13.2 µg) of Ts venom hyaluronidase activity in vitro. In vivo neutralization assays showed that 121.6 µl of anti-hyaluronidase serum inhibited mouse death 100%, whereas 60.8 µl and 15.2 µl of serum delayed mouse death. Inhibition of death was also achieved by using the hyaluronidase pharmacological inhibitor aristolochic acid. Addition of native Ts hyaluronidase (0.418 µg) to pre-neutralized Ts venom (13.2 µg venom+0.94 µl anti-hyaluronidase serum) reversed mouse survival. We used the SPOT method to map TsHyal-1 and TsHyal-2 epitopes. More peptides were recognized by anti-hyaluronidase serum in TsHyal-1 than in TsHyal-2. Epitopes common to both isoforms included active site residues. CONCLUSIONS: Hyaluronidase inhibition and immunoneutralization reduced the toxic effects of Ts venom. Our results have implications in scorpionism therapy and challenge the notion that only neurotoxins are important to the envenoming process.